PROSES BERPIKIR DENGAN KECERDASAN LINGUISTIK DAN KECERDASAN LOGIS-MATEMATIS - Ika Sulistyowati; Sri Rahayu; Nur Fathonah (Universitas PGRI Adi Buana Surabaya, 2015)
This research buildings like by many students are still experiencing difficulty in resolving the problem of the story, problems that arise because of the students still do not understand what is intended in about a story about what is known and what you asked of the questions that in addition to how to solve problems in a sentence mathematics so getting the right answer. Formulation of the problem in this research is Ã¢â‚¬Å“How the thinking of students SMPN 1 Driyorejo in solving story in terms of linguistic and logical-mathematical intelligences?Ã¢â‚¬Â The aim is to describe the thinking of students SMPN 1 Driyorejo in solving story in terms of linguistic and logical mathematical intelligences. The research is a description of qualitative research VIII-D class in SMPN 1 Driyorejo. Subjects in this study consisted of four students with the criteria of two students with linguistic and two students with mathematical logical intelligence. The data obtained by interview, which in a matter of story material tesying functions. The analysis shows that students who have linguistic intelligence can understand about but of less able in model and pursuing that situation and so students not being able to conclude the right answer. Students who have mathematical logical intelligence can understand and capable of being in the model and doing the right with students able to conclude that answers to right. Keywords: thinking process , linguistic intelligence , mathematical logical intelligence, story problem.